(3JMSjf EfLGR GdWdGH (B:s (3EWGQ Yed ef CLd JWhjQ GdeOGQS (B/s - (3OGfjdShf, TGQdhJs; (3GdOLGfj, CeGfjs; (3OGfjdShf, TGQdhJ(B.s ((3GdQjGV (B:s (3GdYHjcGf ddfTQ,s, 2010)
(3ZGdHkG eG jQcR GdeQHhf GdPjf jcQShf hbJge ddEUdGM GdeOQSj Ydi GdYfGUQ GdefaUdI ddJYdje (Bk-12 (3, hgh GdGaJQGV GdQFjSj aj cJGH TGQdhJ OGjfjdShf GdLOjO hGdeDKQ, GdPj jMed YfhGf (B((3JMSjf EfLGR GdWdGH aj GdeOGQS(B)(3; MjK JDcO GdeDdaI Cf GdJRGefG GdUGOb HJWhjQ eOGQSfG jJWdH GdJQcjR Ydi JcGad GdeJZjQGJ GdJj JDKQ Ydi JYde GdWGdH OGNd GdbGYI GdUajI hNGQLgG(B.... (3hjCJj gPG GdcJGH aj KdGKI CLRGA efaUdI, EP JWdYfG OGjfjSdhf aj GdLRA GdChd Ydi fehPL GdOhGFQ GdCQHY ddJYQja HeYGjjQ GdeOQSj GdfGLM, hhabkG dgPG GdfehPL aEfg jfHZj Cf jQJcR cd eG jbhe Hg GdeQqHhf deSGYOI WdHJge Ydi GdJYde Ydi QZHI GdeQHjf (B((3CgOGa GdeOQSI Ch GdebGWYI Ch GdOhdI(B)(3, heYJbOGJge (B((3Gdbje hGdeHGOF(B)(3, heYGQage (B((3GdHMK GdJQHhj(B).s
(3HHdjhLQGajI (B: (3UaMI (B225-230.s
Keywords: (3EOGQI hJfXje GdeOGQSs; (3GdJNWjW GdJQHhjs